Becker muscular dystrophy with dilated cardiomyopathy: A case report. Issue 9 (18th September 2021) - Chen, Yongliang; Zhu, Yunlong; Zhou, Yuying; Zeng, Jianping
Abstract: Becker muscular dystrophy (BMD) complicated with DCM is rare in our daily clinical practice. BMD serves an etiology for heart failure patients due to DCM. Multidisciplinary management is required in this case. Abstract : Becker muscular dystrophy (BMD) complicated with DCM is rare in our daily clinical practice. BMD serves an etiology for heart failure patients due to DCM. Multidisciplinary management is required in this case.